The role of spin–orbit coupling in the electronic structure of iron‐based superconductors. Issue 1 (21st November 2016) - Borisenko, Sergey; Evtushinsky, Daniil; Liu, Zhonghao; Morozov, Igor; Kappenberger, Rhea; Wurmehl, Sabine; Büchner, Bernd; Yaresko, Alexander; Kim, Timur; Hoesch, Moritz; Wolf, Thomas; Zhigadlo, Nikolai
Abstract : Spin–orbit coupling (SOC) is a fundamental interaction in solids that can induce a broad spectrum of unusual physical properties from topologically non‐trivial insulating states to unconventional pairing in superconductors. In iron‐based superconductors (IBS) its role has so far been considered insignificant with the models based on spin‐ or orbital fluctuations pairing being the most advanced in the field. In this review we discuss the recent direct observation of SOC by angle‐resolved photoemission spectroscopy (ARPES). Electron‐like Fermi surface of LiFeAs split by SOC. Abstract : Spin‐orbit coupling is a fundamental interaction in solids that can induce a broad spectrum of unusual physical properties from topologically non‐trivial insulating states to unconventional pairing in superconductors. In iron‐based superconductors, its role has so far been considered insignificant. In this review Borisenko et al. discuss the recent direct observation of spin‐orbit coupling by angle‐resolved photoemission spectroscopy.